1) 4/3:2:2/3

2) = 2:3:1

please explain how to move from step 1 to step two?

Printable View

- Feb 26th 2010, 06:22 AMsaha.subhamPlease explain this step
1) 4/3:2:2/3

2) = 2:3:1

please explain how to move from step 1 to step two? - Feb 26th 2010, 07:16 AMsatx
- Feb 26th 2010, 07:53 AMGrandad
Hello saha.subhamRemember: you can multiply (or divide) every number in a ratio by the same number, without changing the ratio's value.

So:$\displaystyle \frac43:2:\frac23$Have you got it now?$\displaystyle =\frac43\color{red}\times 3\color{black}:2\color{red}\times 3\color{black}:\frac23\color{red}\times 3\color{black}$

$\displaystyle =4:6:2$

$\displaystyle =4\color{red}\div 2\color{black}:6\color{red}\div 2\color{black}:2\color{red}\div 2\color{black}$

$\displaystyle =2:3:1$

Grandad